Polycompartment syndrome – intra-abdominal pressure measurement (Anestezjologia Intensywna Terapia, 2019)
Intra-abdominal hypertension and the abdominal compartment syndrome are well-known, serious, life-threatening clinical entities in acute care surgery. A common characteristic of these syndromes is the permanent and irreversible damage that may affect the organs which can be found inside the given compartment if quick intervention cannot be provided. All factors which may and can lead to a sudden increase in the intra-abdominal pressure can be found among the triggering factors of abdominal compartment syndrome. Despite the modern and quick diagnostics, and the adequate surgical interventions performed in time, the mortality of this syndrome is extremely high (38–71%). It affects practically all vital organ systems: cardiovascular, respiratory, urinary and central nervous system. There are four major compartments in the human body: the head, the chest, the abdomen and the extremities. When two or more compartments have elevated pressures the name of the clinical entity is polycompartment syndrome, first described in 2007. The only possible way of establishing the diagnosis is to measure the intra-abdominal pressure, a widespread manner of which is the measurement through the bladder. Treatment of abdominal and polycompartment syndrome is nearly always surgical decompression with temporary abdominal wall closure or open abdominal treatment. Clinicians need to be aware of the real existence of polycompartment syndrome and the complex and constant interplay of raised pressure between compartments. This highlights the importance of research and development of new intra-abdominal pressure measurement techniques.